1999
DOI: 10.1016/s0014-5793(99)00314-2
|View full text |Cite
|
Sign up to set email alerts
|

Expression and functional analysis of an N‐truncated NifA protein of Herbaspirillum seropedicae

Abstract: In Herbaspirillum seropedicae, an endophytic diazotroph, nif gene expression is under the control of the transcriptional activator NifA. We have over-expressed and purified a protein containing the central and C-terminal domains of the H. seropedicae NifA protein, N-truncated NifA, fused to a His-Tag sequence. This fusion protein was found to be partially soluble and was purified by affinity chromatography. Band shift and footprinting assays showed that the N-truncated NifA protein was able to bind specificall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
32
0
6

Year Published

2000
2000
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 24 publications
4
32
0
6
Order By: Relevance
“…coli strains harboring plasmids pIMA217 and pRAM7 were analyzed for transcriptional activation of the nifHDK:: lacZ fusion. N-truncated NifA (with the first 202 amino acid residues deleted and without the N-terminal domain and the Q-linker) activated transcription of the H. seropedicae nifH promoter in E. coli under low-oxygen conditions (Table 2) regardless of the ammonium levels, as shown previously (25). However, in fnr strain JRG1728 of E. coli, the N-truncated NifA protein failed to activate the H. seropedicae nifH promoter either in the presence or in the absence of oxygen.…”
Section: Resultssupporting
confidence: 82%
See 2 more Smart Citations
“…coli strains harboring plasmids pIMA217 and pRAM7 were analyzed for transcriptional activation of the nifHDK:: lacZ fusion. N-truncated NifA (with the first 202 amino acid residues deleted and without the N-terminal domain and the Q-linker) activated transcription of the H. seropedicae nifH promoter in E. coli under low-oxygen conditions (Table 2) regardless of the ammonium levels, as shown previously (25). However, in fnr strain JRG1728 of E. coli, the N-truncated NifA protein failed to activate the H. seropedicae nifH promoter either in the presence or in the absence of oxygen.…”
Section: Resultssupporting
confidence: 82%
“…A wild-type behavior was observed when strain JRG1728 was transformed with a plasmid carrying the fnr gene (31) expressed from its own promoter. We could not use the fulllength NifA protein in these experiments since it has no activity in E. coli (25,26). On the other hand, as expected, the K. pneumoniae NifA protein was fully active under all conditions tested, including in the fnr mutant (Table 2), since it is not directly sensitive to oxygen or directly dependent on fnr (10).…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…It shows a low level of sequence similarity to the DNA-binding proteins encoded by ntrC from Acidithiobacillus ferrooxidans (Salazar et al, 2001) and nifA from several bacterial species (Monteiro et al, 1999;Gu et al, 2000;Souza et al, 2000). There is no significant similarity beyond that previously noted at the N terminus between AlbA and AlbB from Alcaligenes denitrificans, which also encodes an albicidin-binding protein (Basnayake & Birch, 1995).…”
Section: Resultsmentioning
confidence: 99%
“…Dr. Pedrosa's group also demonstrated that the NifA protein of H. seropedicae, similar to those from the α-Proteobacteria (including A. brasilense), is sensitive to oxygen. Besides, it requires Fe for in vivo activity and the interdomain region between the Cterminal domain and the central domain is involved in oxygen sensitivity (Monteiro et al 1999a). In addition, Dr. Pedrosa's group isolated and characterized the glnB gene of H. seropedicae and determined the three-dimensional structure of the purified protein product, a transducer protein of the PII signal.…”
Section: Genetics Studiesmentioning
confidence: 99%